2014
DOI: 10.1186/1687-1499-2014-206
|View full text |Cite
|
Sign up to set email alerts
|

Priority queueing models for cognitive radio networks with traffic differentiation

Abstract: In this paper, we present a new queueing model providing the accurate average system time for packets transmitted over a cognitive radio (CR) link for multiple traffic classes with the preemptive and non-preemptive priority service disciplines. The analysis considers general packet service time, general distributions for the channel availability periods and service interruption periods, and a service-resume transmission. We further introduce and analyze two novel priority service disciplines for opportunistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Due to different timeliness requirements, the sensors are classified to C classes with different transmission priorities. Suppose that each class c consists of N c sensors and the sensors in class c are assigned with higher transmission priority over any class c > c. Similar to some existing studies [15,23], the data packet flows generated by each class of sensors follow independent Poisson processes with packet generating rate {λ n,c |n = 1, . .…”
Section: Network Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to different timeliness requirements, the sensors are classified to C classes with different transmission priorities. Suppose that each class c consists of N c sensors and the sensors in class c are assigned with higher transmission priority over any class c > c. Similar to some existing studies [15,23], the data packet flows generated by each class of sensors follow independent Poisson processes with packet generating rate {λ n,c |n = 1, . .…”
Section: Network Modelsmentioning
confidence: 96%
“…Multiple channels are used to support parallel transmissions over multiple routing paths to reduce the end-to-end delay of packet delivery. In [23], the authors considered the multipriority multichannel access in cognitive radio environment. Similar to [15], high-priority traffics are allowed to preempt transmission chances of low-priority traffics.…”
Section: Related Workmentioning
confidence: 99%
“…In [11] the authors model the primary user activity as an ON-OFF alternating renewal process and used M/G/1 queuing analysis to obtain the average delay for a single secondary user in presence of primary activity. In [12] the authors use a priority queue model to analyze delay performance of a secondary user with multiple classes of traffic. In [13] the authors use M/D/1 priority queueing scheme to obtain the average delay for primary and secondary users.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-emption and non-preemption priorities attracted many attentions in the previous works. In this topic, we will investigate the authors' contributions in [16][17][18]. A hybrid approach is exposed in [16], at which low priority SUs are no longer pre-empted by high priority SUs, when their number of interruptions reaches a certain threshold value.…”
mentioning
confidence: 99%
“…Therefore, the authors showed that the threshold adjustment according to the performance metric provided a promising performance. In [17], the authors presented a queuing model, providing the accurate average system time, for general packets service time, and service interruption periods, with an opportunistic spectrum access (OSA) networks. They showed that, for the same average CR transmission link availability, the packet system time significantly increases in a semi-static network, with long operating and interruption periods, compared to an OSA network with fast alternating operating, and interruption periods.…”
mentioning
confidence: 99%